The Writing on the Wall … Alzheimer's Disease: A Daughter's Look at Mom's Faithful Care of Dad - Iozzio, M. J. (Journal of religion, disability & health, 2005)
From a reflection on the challenges of providing care for a person with Alzheimer's (AD) disease, a daughter's look at mom's faithful care asks questions of AD disabilities, of virtues, and of the necessary and uniquely human prospects of interdependent/Trinitarian modeling existence. The first question considers the pathology of AD and other complicating health conditions. The second question explores the development of virtues, such as flexibility, stamina, humor, fidelity, and self-care that may enrich care-giving. The third question suggests that the current model ofUS healthcare inadequately finds justice for persons marginalized either by their unwelcome dementia or isolating care-giving.